Yield gap analysis and the factor influencing Binasarisha-4 in some selected areas of Bangladesh - Islam, S; Rahman, M H; Haque, M R; Sarkar, M M A; Sultana, R (Bangladesh Journal of Nuclear Agriculture, 2025)
Binasarisha-4 is a prominent high-yielding mustard variety that plays a crucial role in the oilseed production in Bangladesh. The study was conducted in five major Binasarisha-4 growing areas of Bangladesh, namely Rangpur, Jashore, Tangail, Sirajganj and Magura district to analyze the yield gap and its influencing factors of the variety. In this paper, influencing factors of this crop were analysed by Cobb-Douglas multiple regression equation. The study found that the average yield gap I of Binasarisha-4 production was 0.08 t ha-1 (4.72%) and the average yield gap II was 0.20 t ha-1 (13.35%). Considering all, the average yield gap was 0.28 t ha-1 (17.46%) and much scope for yield enhancement in the variety. The coefficients for power tiller, labor, seed, urea, TSP, MoP, experience, and gypsum were found to be positively significant but farm size negatively significant. By identifying and tackling the causes of the yield gap, this study intends to maximize agricultural productivity, enhance farm incomes, and strengthen national self-sufficiency in edible oil. Bangladesh J. Nuclear Agric., 39(1): 155-165, 2025